Analysis of Imbalance Loads and Losses Based on The Largest Loading by 3 Units of 3 Phase Distribution Transformer - Zulfatri Aini; Esa Mutari; Liliana Liliana; Oriza Candra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2021)
The imbalance load of distribution transformers often occurs.This is due to the fact that the load time amongst consumers is not the same, so that there is a difference in the value for each R, S, and T phase. The value difference of the phase causes overload in several phases so as the current emerges in neutral transformers. The current flowing in the neutral transformers causes the losses. In this research, the identification of the overload and the calculation of the distribution transformer load with the IEC reference standard which is allowed for 80% and the calculation of the imbalance transformer load with the 5% standard, then the losses resulting from the presence of neutral currents were carried out. There are three transformers in the Hangtuah feeder that have a load exceeded the standard, namely the DRI 0157, DRI 0241, and DRI 0065 transformers. The calculations for the three transformers are taken from measurement data in the form of voltage and current values for each phase during the daytime and nighttime and are simulated using ETAP 12.6.0 software. The symmetrical component method was used to obtain the imbalance value of the transformer load based on the measurement results and the ETAP simulation. The result of this research is the imbalance load occured in the three transformers. DRI 0241 is the transformer that has the largest percentage of an imbalance load at night. At nighttime, based on the measurement results of the DRI 0241, the transformer load is 80% and 65% at daytime, while for the imbalance load at nighttime and daytime are 32.2% and 29.8%, respectively. The greater the loading of the transformer, the larger the imbalance loading of transformer becomes. The current in neutral transformer generated losses in the amount of 45 A and 2.4% at nighttime while for 33 A and 1.2% at daytime. The neutral current affects the values of losses that the higher it is, the bigger the losses appear in a transformer.